Accessibility, textbooks, and Access Services. Issue 3 (3rd July 2017) - Kahler, Janice E.
ABSTRACT: Putting access in Access Services is the goal. The Course Reserves unit is the place. Textbooks are the focus. Electronic technologies are the future. Patron-centric services will be our standard. Access to textbooks by all patrons will be the achievement. Course Reserves located in Library West at the University of Florida George A. Smathers Libraries has begun policies and procedures to enhance the patron experience based on specific needs using programs, technologies, and particular attention to customer service. This article explores providing services for accessible electronic textbooks to patrons who have specific needs such as blindness or low vision.